Perception of the Costumers Across District Regarding Delays in Goods By Delivery Services - Darmawan, Indra Angki (Ghaly: Journal of Islamic Economic Law, 2024)
This research analysis the high public need for goods delivery services, which has becomea business opportunity for expedition business players. This can be seen from the largenumber of companies expanding their wings in the field of goods delivery. In Indonesiaitself, the goods delivery service industry is a business prospect whose economic growthrate is growing rapidly from year to year. Not only private companies, but state- ownedcompanies are also taking part in improving themselves and implementing a number ofconveniences in goods delivery services. This research aims to, first, find out theperception of the people of Samarinda Across District regarding delays in goods bydelivery services. Second, understand the review of Law Number 8 of 1999 Article 4regarding delays in goods by delivery services. This research is field research usingqualitative descriptive methods. With an empirical normative research approach. As fordata collection techniques using observation, interviews and documentation methods,the research location is the community of Samarinda Seberang subdistrict. The subjectof the research is the Samarinda Seberang District Community, and the object of thisresearch is goods delivery services. The results of the research show that the people ofSamarinda Seberang Subdistrict commented on the goods delivery expedition servicewhich, when sending the goods they ordered, sometimes did not meet the specified time.The people of Samarinda Seberang Subdistrict felt disappointed by the delay in goodswhich did not meet the specified time. However, the people of Samarinda SeberangDistrict do not receive compensation or compensation from the goods delivery servicesthey use. The people of Samarinda Seberang District should have the rights as intendedin Law Number 8 of 1999 Article 4, and business actors are also responsible for providingcompensation as stated in referred to in Law Number 8 of 1999 Article 19.